How Preferences of General Medicine Students for Specialty Choice Are Affected? a qualitative study - Mehdi Heidari; Mahmoud Keivanara; Maryam Moeeni (پژوهش‌های سلامت‌محور, 2019)
How Preferences of General Medicine Students for Specialty Choice Are Affected? a qualitative study